Analisis Perbandingan Metode Economic Order Quantity (EOQ) Dan Metode Tradisional Dalam Pengendalian Persediaan Bahan Baku Pada Usaha Mie Basah Kediri - Adelia Dewi Pratama; Trisnia Widuri; Zulfia Rahmawati (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the effectiveness of raw material inventory control at the Kediri Wet Noodle business by comparing the traditional method with the Economic Order Quantity (EOQ) method. A descriptive quantitative approach was applied, utilizing EOQ, Safety Stock (SS), Re-order Point (ROP), and total inventory cost analysis. The results indicate that the traditional method leads to 24 purchase cycles per year with an inventory cost of IDR 4,320,000, without considering safety stock or re-order points. In contrast, the EOQ method shows an optimal purchase quantity of 1,421 sacks (35,525 Kg) with five purchase cycles per year, an inventory cost of IDR 574,455, a Safety Stock of 67 sacks (1,675 Kg), and a Re-order Point of 107 sacks (2,675 Kg). Therefore, the EOQ method reduces inventory costs by up to 86% compared to the traditional method. Nevertheless, its limitation lies in the exclusion of raw material shelf life and storage condition factors.